Diversity of Lactic Acid Bacteria Isolated from Indonesian Traditional Fermented Foods - APON ZAENAL MUSTOPA; FATIMAH FATIMAH (Indonesian Society for microbiology, 2014)
The diversity of lactic acid bacteria was evaluated from Indonesian fermented foods such as dadih (buffalo fermented milk), tempoyak (fermented durian), bekasam (fermented meat), and tape ketan (fermented glutinous rice). Lactic acid bacteria were enumerated using selective media and characterised based on a genotypic methods such as rep- PCR and RAPD-PCR, as well as 16S rRNA gene sequencing of representative strains. Forty-six colonies had successfullybeen isolated from Indonesian fermented foods. The great majority of these colonies originated from dadih (43.48%), tempoyak (39.13%), bekasam (13.04%) and tape (4,3%). The 46 isolates were characterised based on a genotypic methods such as RAPD and rep-PCR as well as 16S rRNA gene sequencing of representative strains. The rep-PCR result yielded seven clusters (I-VII) at a similarity level of 75-88% and RAPD-PCR used LB2 primer, M13 primer and primer A, B, C. The RAPD result using LB2 primer yielded eight clusters (I-VIII) at a similarity level of 82-91%. Identification using 16S rRNA showed that the majority strains as Lactobacillus plantarum, Lactobacillus fermentum and Pediococcus pentosaceus strains.